PENENTUAN KUAT TEKAN JANGKA PANJANG PILAR BATUBARA SILICIFIED DENGAN UJI RAYAPAN BEBAN BERTAHAP DI LABORATORIUM - Novi Hartami, Pantjanita
Abstrak : The stability of an underground opening is influenced by a number of factors, including creep behavior of rock. Creep on pillar will take place due to the long term load applied. Consequently, it would be interesting to understand the time dependent behaviour of coal pillar by creep tests. Samples of the creep test were obtained from Bukit Asam coal mining, in Tanjung Enim, South Sumatra. The sample prepared in form of cylindrical specimens with slenderness ratio of 1 : 1 and diameters were 54 mm, 70 mm, 100 mm, and 150 mm. The creep tests were carried out based on multi stage constant load method (Vyalov, 1986). Sample was subject to a constant load for certain period of time, and afterwhich another constant load, higher than that of the previous one was applied until failure took place. During the test period, axial and lateral deformations were monitored using two dial gauge electronics and connected to a computer from which continuous data collecting could be obtained Axial strain-time curves revealed that the behavior of the coal samples followed Burger model. The rheological constants recorded from the creep tests are as follows : Diameter Longterm El E2 nl *12 (mm) Strength 103 (MPa) 103 (MPa) 103 1o3 (% o) (MPa.hour) (MPa.hour) 54 100 3.17 - 4.27 130 - 600 930 - 6090 67.9 - 1150 70 95 2.96 - 5.35 16.9 - 372 2060 - 42900 26.5 - 1210 100 85 2.91 -12.5 197 - 4590 9300 - 223000 178 - 212000 150 80 1.52 - 2.82 151 - 1500 2000 - 110000 761 - 32700 Scale factor was obtained to extrapolate laboratory data to the real condition by means dimensional analysis. When the area of the real pillar was x times of that of the model, the scale factors of the pillar height, uniaxial compression strength, longterm strength, modulus of elasticity, and delayed elasticity were the same, i.e. x0.5, whereas that of rate of viscous flow and rate of delayed elasticity being xi,\'